2018
DOI: 10.3389/fmicb.2018.02409
|View full text |Cite
|
Sign up to set email alerts
|

Host Phylogeny Is a Major Determinant of Fagaceae-Associated Ectomycorrhizal Fungal Community Assembly at a Regional Scale

Abstract: Environmental filtering (niche process) and dispersal limitation (neutral process) are two of the primary forces driving community assembly in ecosystems, but how these processes affect the Fagaceae-associated ectomycorrhizal (EM) fungal community at regional scales is so far poorly documented. We examined the EM fungal communities of 61 plant species in six genera belonging to the Fagaceae distributed across Chinese forest ecosystems (geographic distance up to ∼3,757 km) using Illumina Miseq sequencing of ITS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 80 publications
11
39
0
Order By: Relevance
“…Environmental filtering (niche process) and dispersal limitation (neutral process) are two of the fundamental processes in structuring biotic community assembly (Cottenie, 2005). The effect of environmental filtering by host plants (e.g., identity and phylogeny) on root-associated fungal communities has been widely documented in previous studies (e.g., Ishida et al, 2007;Tedersoo et al, 2013;van der Linde et al, 2018;Wu et al, 2018;Schroeder et al, 2019;Sepp et al, 2019;Wang et al, 2019a,b). For example, plant identity significantly shaped rootassociated ectomycorrhizal (EM) fungal communities (Ishida et al, 2007;Tedersoo et al, 2012;van der Linde et al, 2018) and arbuscular mycorrhizal (AM) fungal communities (Martinez-Garcia et al, 2015;Ciccolini et al, 2016;Zheng et al, 2016;Sepp et al, 2019) through host specificity, generating diverse substrates and changing microhabitats (Wardle, 2006;Dickie, 2007;Aponte et al, 2010).…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations
“…Environmental filtering (niche process) and dispersal limitation (neutral process) are two of the fundamental processes in structuring biotic community assembly (Cottenie, 2005). The effect of environmental filtering by host plants (e.g., identity and phylogeny) on root-associated fungal communities has been widely documented in previous studies (e.g., Ishida et al, 2007;Tedersoo et al, 2013;van der Linde et al, 2018;Wu et al, 2018;Schroeder et al, 2019;Sepp et al, 2019;Wang et al, 2019a,b). For example, plant identity significantly shaped rootassociated ectomycorrhizal (EM) fungal communities (Ishida et al, 2007;Tedersoo et al, 2012;van der Linde et al, 2018) and arbuscular mycorrhizal (AM) fungal communities (Martinez-Garcia et al, 2015;Ciccolini et al, 2016;Zheng et al, 2016;Sepp et al, 2019) through host specificity, generating diverse substrates and changing microhabitats (Wardle, 2006;Dickie, 2007;Aponte et al, 2010).…”
Section: Introductionmentioning
confidence: 97%
“…For example, plant identity significantly shaped rootassociated ectomycorrhizal (EM) fungal communities (Ishida et al, 2007;Tedersoo et al, 2012;van der Linde et al, 2018) and arbuscular mycorrhizal (AM) fungal communities (Martinez-Garcia et al, 2015;Ciccolini et al, 2016;Zheng et al, 2016;Sepp et al, 2019) through host specificity, generating diverse substrates and changing microhabitats (Wardle, 2006;Dickie, 2007;Aponte et al, 2010). Likewise, an increasing amount of studies have indicated that host phylogeny strongly predicts root-associated fungal communities, such as total (Wehner et al, 2014;Schroeder et al, 2019), EM (Põlme et al, 2013;Tedersoo et al, 2013;Wu et al, 2018;Wang et al, 2019a), AM (Wang et al, 2019b), pathogenic (Schroeder et al, 2019;Wang et al, 2019b), and saprotrophic (Schroeder et al, 2019) fungi. According to phylogenetic niche conservatism, closely related plants are more similar in morphological and functional traits than distantly related ones (Losos, 2008), and maybe tend to associate with more similar fungal partners.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, in some pioneer studies the geographic distributions of ECM fungal communities at regional and/or continental scales were investigated (ranging from hundreds to thousands of kilometers). From these studies, it was revealed that species identity or phylogeny of host trees are one of the most important factors generating geographic structures of ECM fungal communities (Põlme et al , 2013; Roy et al 2013; van der Linde et al , 2018; Wu et al , 2018). Unlike free-living organisms, host-associated microbial communities like ECM fungi often exhibit biogeographic patterns that are related to the distribution of their hosts (Martiny et al , 2006), because of co-migration of microbes with their host species to new habitats (Kennedy et al , 2011).…”
Section: Introductionmentioning
confidence: 99%